Forty-year multi-scale land cover change and political ecology data reveal a dynamic and regenerative process of forests in Peruvian Indigenous Territories - Bennett, A.; Larson, A.M.; Zamora Ríos, A.; Monterroso, I.; Sheila, G. (Elsevier, 2023)
This article explores deforestation and reforestation dynamics over 415,749 hectares of 25 titled Indigenous Community Lands (ICLs) in the Peruvian Amazon over forty years at three scales: total area, regions, and communities. We focus on ICLs as the territorial unit of analysis, as they are increasingly discussed regarding their importance for conservation. Additionally indigenous communities (ICs) are a too-marginalized group in the Amazon that merit more attention. Analyses of this kind are often short-term and use only large-scale Earth Observation methodologies. We use a multi-method approach linking remote sensing with ground verification, and qualitative historical political ecology work with ICs. We find that overall accumulated deforestation was low at 5%, but that when reforestation is considered, net deforestation was only 3.5%. At the community level deforestation and afforestation dynamics are complex, except for one period that indicates a macro state driver in the region. Results suggest inadequate accounting for forest regeneration in deforestation analyses and challenge the notion that presenting stakeholders with accumulated forest loss values is helpful in tropical areas where forests and people are dynamic. Furthermore, our work with communities highlights that categorizing them and their lands as pro-environment or not in general terms is unhelpful for determining fund flows to ICLs for environmental or development purposes.